Diavola - Thorne, Jennifer (Nightfire, Tor Publishing Group, 2024)
Anna has two rules for the annual Pace family destination vacations: Tread lightly and survive. It isn't easy when she's the only one in the family who doesn't quite fit in. Her twin brother, Benny, goes with the flow so much he's practically dissolved, and her older sister, Nicole, is so used to everyone--including her blandly docile husband and two kids--falling in line that Anna often ends up in trouble for simply asking a question. Mom seizes every opportunity to question her life choices, and Dad, when not reminding everyone who paid for this vacation, just wants some peace and quiet. The gorgeous, remote villa in tiny Monteperso seems like a perfect place to endure so much family togetherness, until things start going off the rails--the strange noises at night, the unsettling warnings from the local villagers, and the dark, violent past of the villa itself. (Warning: May invoke feelings of irritation, dread, and despair that come with large family gatherings.).